2021
DOI: 10.1159/000517373
|View full text |Cite
|
Sign up to set email alerts
|

WT1 Pathogenic Variants are Associated with a Broad Spectrum of Differences in Sex Development Phenotypes and Heterogeneous Progression of Renal Disease

Abstract: Wilms’ tumor suppressor gene 1 (<i>WT1</i>) plays an essential role in urogenital and kidney development. Heterozygous germline pathogenic allelic variants of <i>WT1</i> have been classically associated with Denys–Drash syndrome (DDS) and Frasier syndrome (FS). Usually, exonic pathogenic missense variants in the zinc finger region are the cause of DDS, whereas pathogenic variants affecting the canonic donor lysine-threonine-serine splice site in intron 9 cause FS. Phenotypic overlap bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
1
6
0
1
Order By: Relevance
“…This is the first reported familial case of a pathogenic variant of WT1 ZF4. In the earlier reported cases, all nine 46,XX cases of the WT1 ZF4 variants were de novo and exhibited testicular or ovotesticular DSD with atypical external genitalia [Gomes et al, 2019;Eozenou et al, 2020;Sirokha et al, 2021;Ferrari et al, 2022]. Consistently, with the above cases, our proband case showed a similar DSD phenotype.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is the first reported familial case of a pathogenic variant of WT1 ZF4. In the earlier reported cases, all nine 46,XX cases of the WT1 ZF4 variants were de novo and exhibited testicular or ovotesticular DSD with atypical external genitalia [Gomes et al, 2019;Eozenou et al, 2020;Sirokha et al, 2021;Ferrari et al, 2022]. Consistently, with the above cases, our proband case showed a similar DSD phenotype.…”
Section: Discussionsupporting
confidence: 89%
“…This family case suggests that the clinical phenotypes of the WT1 ZF4 variant can be broad in spectrum, ranging from mild reproductive organ defects with normal fertility to sex-reversed DSD or normal renal function to chronic kidney disease (CKD) (Table 1). reported cases (n = 9) [Gomes et al, 2019;Ferrari et al, 2022;Eozenou et al, 2020;Sirokha et al, 2021] present study reported case (n = 1) [Eozenou et al, 2020] present The broad clinical spectrum of 46,XX testicular/ovotesticular DSD cases, as WT1 ZF4 variants, is also reported in the missense variant p.R92W of the NR5A1 gene [Bashamboo et al, 2016;Baetens et al, 2017;. NR5A1 plays an essential role in gonadogenesis and male sex determination and is classically known as one of the most common causative genes for 46,XY DSD [Morohashi et al, 1992;Achermann et al, 1999;Ono and Harley, 2013].…”
Section: Discussionmentioning
confidence: 74%
“…M154V mutation of KHDRBS1 (KH RNA binding domain containing, signal transduction associated 1) may result in AS of genes involved in DNA replication and repair, which may affect DNA repair of granulosa cells and/or oocytes, ultimately leading to POI [167]. New WT1 variant-related phenotypes, such as primary ovarian insufficiency, have also been reported, which further emphasizes the status of WT1 in the pathogenesis of POI [168]. Another group compared the fertility of Tet1-lacking mice throughout their reproductive years.…”
Section: The Findings Of Single-cell Studies In Pathology Of Follicul...mentioning
confidence: 99%
“…WT1 abnormalities may also be present in non-syndromic patients [Ferrari et al, 2022]. Usually, WT1 renal disease is manifested by a progressive glomerulopathy associated with younger age at onset (infancy or childhood), but a slow progression of the renal disease, and its manifestations in patients not so young may also occur.…”
Section: Wt1 Disordersmentioning
confidence: 99%